Media in guidance and counseling services: a tool and innovation for school counselor - Said Alhadi; Agus Supriyanto; Devita Ayu Mei Dina (Indonesian Counselor Association (IKI), 2016)
Guidance and counseling services is an element of education that aims to support the achievement of the objectives of education. Guidance and counseling can prevent students experience problems and may even alleviate student of his problems. One of the efforts that need to be done to improve the effectiveness of guidance and counseling services is the development of media guidance and counseling. Media guidance and counseling can make different colors of guidance and counseling services so that the interests of students increase when following the guidance and counseling services. Used media must be relevant with the objectives/ competency of the guidance and counseling and relevant with material guidance and counseling services. Media in guidance and counseling services plays an important role in the implementation of guidance and counseling so that student can better understand, understand, and internalize the material guidance and counseling services to the student.